1992
DOI: 10.1007/bf02220609
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine lessens the incidence of mortality in L-Dopa-treated parkinsonian patients: Prado-study discontinued

Abstract: L-Dopa supplemented by a peripheral decarboxylase inhibitor is considered the most potent therapeutic regimen prolonging active life in Parkinsonian patients. The long-term benefit of therapy is limited by adverse effects, such as dyskinesia and on-off phenomena, which can be mitigated by the concomitant administration of dopamine agonists, such as bromocriptine. In order to quantify the beneficial impact of early combination therapy, a controlled clinical trial (PRADO: PRA videl1 + DO pa) in patients with ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
2

Year Published

1994
1994
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 24 publications
1
27
2
Order By: Relevance
“…The increase in the cardiac sympathetic tone (as indicated by higher values of the LF component), observed after acute oral bromocriptine, seems to be in disagreement with the finding of a reduction in cardiac sympathetic activity in L-dopa-treated patients with Parkinson's disease given bromocriptine, as reported by Przuntek et al 1 This discrepancy can probably be related to the fact that (unlike Przuntek et al) we evaluated the drug effects after an acute and not a chronic administration and with healthy subjects rather than those in disease conditions. However, further investigations are needed to assess the dopaminergic modulation of the cardiac sympathetic drive after chronically administered bromocriptine.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The increase in the cardiac sympathetic tone (as indicated by higher values of the LF component), observed after acute oral bromocriptine, seems to be in disagreement with the finding of a reduction in cardiac sympathetic activity in L-dopa-treated patients with Parkinson's disease given bromocriptine, as reported by Przuntek et al 1 This discrepancy can probably be related to the fact that (unlike Przuntek et al) we evaluated the drug effects after an acute and not a chronic administration and with healthy subjects rather than those in disease conditions. However, further investigations are needed to assess the dopaminergic modulation of the cardiac sympathetic drive after chronically administered bromocriptine.…”
Section: Discussioncontrasting
confidence: 65%
“…Key Words: autonomic nervous system Ⅲ sympathetic nervous system Ⅲ dopamine Ⅲ heart rate B romocriptine is a D 2 -like receptor agonist that is known to inhibit sympathetic output and to lower the cardiovascular mortality in L-dopa-treated patients with Parkinson's disease. 1 The cardioprotective effect of bromocriptine can be related to a withdrawal of the cardiac sympathetic activity, which could diminish the risk of potentially lifethreatening ventricular arrhythmias. As a matter of fact, it has been shown in experimental animals that bromocriptine increases the ventricular fibrillation threshold by 50% 2 and decreases plasma levels of catecholamines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Despite these encouraging results, there are relatively few pharmacoepidemiological data on the effectiveness of such combination therapy against mortality in PD. 1 The Prado study 6 reported a significant decrease in mortality risk under bromocriptine plus levodopa (versus levodopa alone), whereas the Sydney multicentre study (investigating levodopa-carbidopa versus low-dose bromocriptine) failed to find any significant action of bromocriptine on mortality or progression of the disease. 7 The aim of the present study was to compare, in terms of mortality, two treatment regimens for PD, i.e., bro-*Correspondence to: Professor Jean-Louis Montastruc, Service de Pharmacologie Clinique, Faculté de Médecine, 37 allées Jules-Guesde, 31073 Toulouse Cedex, France.…”
mentioning
confidence: 97%
“…Symptomat ic treatments may also improve prognosis by means other than neuroprotection. For example, reduced cardiovascu lar catastrophies have been reported in patients taking bromocriptine with levodopa compared with levodopa alone [15], It seems unfortunate to exclude evaluation of these treatments as protective agents in an attempt to sim plify the interpretative process.…”
Section: Deprenyl and The Issue Of Neuroprotectionmentioning
confidence: 99%